Revisiting public health informatics: patient privacy concerns. Issue 2 (4th June 2018) - Birnbaum, David; Gretsinger, Kathryn; Antonio, Marcy G.; Loewen, Elizabeth; Lacroix, Paulette
Abstract : Purpose: Expanding networks of data portals and repositories linked to electronic patient record systems, along with advances in information technology, have created both new opportunities in improving public health and new challenges in protecting patient privacy. The purpose of this paper is to review stakeholder perspectives and provide a framework for promoting implementation of current privacy protection improvement recommendations. Design/methodology/approach: This paper summarizes a workshop session discussion stemming from the 2017 Information Technology and Communication in Health (ITCH) biennial international conference in Victoria, British Columbia, Canada. The perspectives within health service research, journalism, informatics and privacy protection were represented. Findings: Problems underlying gaps in privacy protection in the USA and Canada, along with then-current changes recommended by public health leaders as well as Information and Privacy Commissioners, were identified in a session of the 2015 ITCH conference. During the 2017 conference, a workshop outlined the current situation, identifying ongoing challenges and a lack of significant progress. This paper summarizes that 2017 discussion identifying political climate as the major impediment to progress on this issue. It concludes with a framework to guide the path forward. Originality/value: This paper provides an international perspective to problems, resources and solution pathways with links useful to readers in all countries.